2020
DOI: 10.3889/oamjms.2020.4019
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between Histopathology Type and Neoadjuvant Chemotherapy Response for Cervical Cancer Stage IB2 and IIA2

Abstract: BACKGROUND: Cervical cancer was the fourth common women cancer in the world and the second most in Indonesia. Chemotherapy has been evaluated as a therapy strategy to treat cervical cancer stage IB2 and IIA2 prior the radical hysterectomy. Neoadjuvant chemotherapy was still being a controversy for the chemotherapy resistance patient and will delay the definitive therapy. A marker is needed to identify patient which more relatively resistant to chemotherapy. Squamous cell carcinoma (SCC) type was known to have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 33 publications
1
2
0
Order By: Relevance
“…However, only the difference in response to neoadjuvant chemotherapy at ER hormone receptors was statistically significant in this study (p = 0.025, OR = 4.5). 20 The distribution of results was similar to that of other researchers. Another study in Ki67, Prihantono et al In 2017 found that Ki67 had a strong positive correlation with neoadjuvant chemotherapy response, while Zhao et al found that Ki67 and HER2 could significantly predict disease free survival (DSF) and ER, PR, HER2-neu, Ki67 can predicted overall survival (OS).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…However, only the difference in response to neoadjuvant chemotherapy at ER hormone receptors was statistically significant in this study (p = 0.025, OR = 4.5). 20 The distribution of results was similar to that of other researchers. Another study in Ki67, Prihantono et al In 2017 found that Ki67 had a strong positive correlation with neoadjuvant chemotherapy response, while Zhao et al found that Ki67 and HER2 could significantly predict disease free survival (DSF) and ER, PR, HER2-neu, Ki67 can predicted overall survival (OS).…”
Section: Discussionsupporting
confidence: 88%
“…In line with this study, Muhammad et al In 2020 also found a significant relationship between parity> 3 and response to neoadjuvant chemotherapy with an OR value of 10.8. 20 Fortner et al In 2019 also found the same thing where parity ≥ 3 had a worse chemotherapy response compared to patients with parity <3. Parity at risk increases the risk of negative hormone receptors that can worsen the response to neoadjuvant chemotherapy.…”
Section: Discussionmentioning
confidence: 86%
“…17,20 Radiotherapy response can also be caused by other factors, including Hb level when diagnosed with cervical cancer, type of treatment (radiation or chemoradiation), and the degree of differentiation of histopathological types. 18,22,23 Acute toxicity are related to technique, total dose, volume, duration of radiation therapy, hygiene, and patient nutrition, including socioeconomic conditions. In this study, the most toxicity of external radiotherapy were hematological toxiciy (45.8%) followed by skin toxiciy (45.3%), gastrointestinal toxicity (6.3%) and urinary tract toxicity (2,6 %).…”
Section: Table 3 Response Analysis To External Radiotherapy Based On ...mentioning
confidence: 99%